Thong-Bhitongan: Development of Educational Media based on Ethnomatematics of Madura Coastal Culture - Tita Tanjung Sari (STAI Hubbulwathan Duri, 2023)
This study is aimed to develop mathematics learning media inspired by the typical games of the coastal communities of Sumenep Madura Regency. We provide the media with